Lawyers, Historians, Ethics and the Judicial Process - Boast, Richard (Victoria University of Wellington Law Review, 1998)
The calls on an advocate’s loyalty in court are several and sometime’s conflicting. In this article Richard Boast observes that in tribunals, and particularly the Waitangi Tribunal, these conflicts are often magnified. He then proceeds to critique, partly from his own experiences, the role of both lawyers and historians in such a forum, concluding that the increased tensions are largely due to changes in the procedures in the Tribunal incident on the pressure from clients to see their causes vigorously pursued.